Experimental evidence for the genetic benefits of female mate choice in the monandrous wolf spider Pardosa astrigera. (October 2018) - Wu, Qijia; Wen, Lelei; Chen, Jian; Li, Daiqin; Jiao, Xiaoguo
Abstract : Material and/or genetic benefits are hypothesized to be the main drivers of female mate choice. Research on female mate choice has mainly focused on polyandrous species and has seldom considered monandrous species. Given the absence of postcopulatory mate choice in monandrous females, we predicted that precopulatory mate choice is important for monandrous species. Using the wolf spider Pardosa astrigera as a model monandrous species, we compared mating, reproductive output and offspring fitness between females with preferred mates (mates that were accepted on the first exposure) and females with nonpreferred mates (mates that were rejected on the first exposure but were induced to mate on the second exposure). Our results showed that the mating duration, latency to egg laying and to egg hatching, fecundity and egg hatching rate did not differ significantly between females with preferred versus nonpreferred mates. In contrast, female and male development time was significantly shorter and female carapace width was significantly greater for offspring of females with preferred versus nonpreferred mates. In addition, survival from egg hatching to maturity was twice as high for offspring of females with preferred mates. These results indicate that female mate choice by the monandrous P. astrigera provides genetic rather than material benefits. Highlights: We explored the benefits of female mate choice in a monandrous wolf spider. No differences in female reproduction were found between the two mating groups. Offspring from the preferred females developed faster and survived better. The benefits for offspring from female mate choice contributed to genetic benefits.